Silyl-Heck Reactions for the Preparation of Unsaturated Organosilanes - Martin, Sara E. S.; Watson, Donald A. (Synlett, 2013)
Few methods exist to directly install silyl functionality onto olefins. This Synpacts article highlights the state of the art of the silyl-Heck reaction and our recently developed conditions for preparing allyl and vinyl silanes from terminal alkenes using this method.
Keywords: allyl silane; vinyl silane; silyl-Heck reaction; alkene; palladium